Pengaruh Literasi Keuangan dan Literasi Digital Terhadap Minat Mahasiswa Universitas Sari Mulia Menggunakan Bank Digital - Rika Yuliyanti; Suzi Suzana; Adista Anjar Diany (Komunitas Dosen Indonesia, 2026)
Digital banks emerged as a response from commercial banks to the development of information technology and people's lifestyles in the digital era. The existence of digital banks in Indonesia is demonstrated by the increase in digital bank users from 2021 to 2033 and is predicted to continue to increase until 2026. The development of the digital financial services industry can pose a threat to communities with minimal financial and digital literacy. The purpose of this study was to investigate the influence of financial and digital literacy on the interest of Sari Mulia University students in using digital banks. This study was quantitative, involving 100 respondents. Respondents were selected using simple random sampling techniques. Data were analysed using multiple linear regression techniques. Hypotheses were tested through F-tests and t-tests. The results of the study stated that financial literacy and digital literacy influenced the interest of Sari Mulia University students in using digital banks.